Non-destructive Inspection of Composite Aileron during Fatigue Test - Podstawka Michal (EDP Sciences, 2021)
The operational safety and reliability of an airplane must be an integral part of its design. The use of suitable materials that pass material certification tests is very important for a new aircraft design. The next part is testing specific samples, sub-components, and components such as the aileron. The paper deals with a non-destructive evaluation of composite primary structural part fatigue tests in accordance with damage tolerance philosophy considering impact damage presence. NDT methods such as visual, eddy current, and ultrasonic testing included phased array technique, are used for the inspections. A schedule of inspections was created, and structural durability was verified.